Examples of individual supported living for adults with intellectual disability - Cocks, Errol; Thoresen, Stian; O'Brien, P.; McVilly, K.; Thomson, Allyson; Gadow, F.; Crosbie, J.; Prain, M. (2016)
Background: This article provides a qualitative account of four models of support for adults with intellectual disability in individual supported living (ISL) arrangements. Materials and Methods: Completion of the first 50 evaluations of 150 arrangements for the third phase of the ISL project provided the examples. Results: Four approaches are described: living alone, co-residency, relationship and host family. Within each type, wide variations occur particularly based on security of tenure, formal and informal support and management variations. Conclusion: Fifty evaluations so far illustrated a wide range of approaches to ISL, providing evidence of the critical importance of the formal and informal support environment and reinforcing the contention that ISL is appropriate for people with high support needs.